Brainard, Marcus, State Belief and its Neutralization. Husserl's System of Phenomenology in Ideas I ,University of New York Press, 2002, 331 págs - Leocata, Francisco (2005)
Fil: Leocata, Francisco. Pontificia Universidad Católica Argentina. Facultad de Filosofía y Letras; Argentina